2022
DOI: 10.3390/cancers14010212
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Involvement in Early-Stage Cervical Cancer: Is Lymphangiogenesis a Risk Factor? Results from the MICROCOL Study

Abstract: Background: In patients with cervical cancer, the presence of tumoral lymph-vascular space invasion (LVSI) is the main risk factor for pelvic lymph node metastasis (PLNM). The objective of this study was to evaluate the presence of several markers of lymphangiogenesis in early-stage cervical cancer and their correlation with PLNM and tumoral recurrence. Materials and Methods: Seventy-five patients with early-stage cervical carcinoma underwent sentinel lymph node (SLN) sampling in association with complete pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…In this study, based on 2009 staging, there was a negative effect of LVSI on 5‐year OS in the after‐PSM subgroup of tumors ≤4 cm in diameter. Previous research has indicated that tumor LVSI is a significant risk factor for the metastasis of pelvic lymph nodes in cervical cancer 31 . Also, lymph node metastasis was a risk factor for 5‐year DFS in all three groups in the FIGO2009 staging.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this study, based on 2009 staging, there was a negative effect of LVSI on 5‐year OS in the after‐PSM subgroup of tumors ≤4 cm in diameter. Previous research has indicated that tumor LVSI is a significant risk factor for the metastasis of pelvic lymph nodes in cervical cancer 31 . Also, lymph node metastasis was a risk factor for 5‐year DFS in all three groups in the FIGO2009 staging.…”
Section: Discussionmentioning
confidence: 68%
“…Previous research has indicated that tumor LVSI is a significant risk factor for the metastasis of pelvic lymph nodes in cervical cancer. 31 Also, lymph node metastasis was a risk factor for 5-year DFS in all three groups in the FIGO2009 staging. Therefore, this group of patients should be treated with active adjuvant therapy postoperatively to improve their survival rate.…”
Section: Discussionmentioning
confidence: 81%
“…A surgical approach limiting a complete PALN dissection by using a combined primary pelvic and secondary para-aortic sentinel lymph node mapping technique, as reported here in our study, could reduce the potential risks and morbidity associated with this procedure, especially in the presence of increased surgical risk factors such as in obese and frail elderly patients ( 35 ). Similar to the primary pelvic sentinel lymph nodes, histologic ultrastaging using immunohistochemistry for identifying micrometastasis could be applied to the secondary para-aortic sentinel lymph nodes ( 36 ). A PALN dissection is especially indicated for patients with LACC and/or those with suspicious pelvic LNs but apparent normal para-aortic LNs on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastases (LNM) are routes of CC dissemination. LNM is a poor prognostic feature, even in patients with early-stage disease ( 70 ). The evaluation of preoperative LNM is based on medical imaging, which has limitations.…”
Section: Proteins As Predictive Biomarkers In CCmentioning
confidence: 99%